Einfluss des Bindungsverhaltens auf chronischen und somatoformen Schmerz = Impact of attachment behavior on chronic and somatoform pain - Pfeifer, Ann-Christin; Ehrenthal, Johannes C.; Neubauer, Eva; Gerigk, Carina; Schiltenwolf, Marcus (Der Schmerz, 2016)
In addition to being a risk factor for the course of chronic pain, the personality characteristics of the individual attachment style are also predictors for the success of medical and psychosocial interventions and aspects of the physician-patient relationship. Insecurely attached patients seem to be less able to sustain the positive effects of pain therapy. These results are especially relevant as insecure attachment patterns are overrepresented among chronic pain patients. As a result the attachment style can be seen as a psychosocial vulnerability factor for the chronification of acute pain.
Gesehen am 29.08.2017